MANAGEMENT IDENTIFICATION AND COACHING PATTERN OF ANGKATAN MUDA SEYEGAN (AMS) SOCCER SCHOOL IN FOSTERING AN EARLY AGE PLAYERS (BETWEEN THE AGES OF 10-13 YEARS OLD) - Fathan Nurcahyo (Jorpres (Jurnal Olahraga Prestasi), 2016)
The aim of this research is to identify the management and the coaching pattern of Angkatan Muda Seyegan soccer school in fostering the early age players in the age of 1 0-13 years old in Gendengan, Margodadi, Seyegan Sleman Yogyakarta. This is a descriptive qualitative research where the technique used was interview, observation, and documentation study. The research subject were the director of AMS soccer school (1 person), coach (1 person), the member of the soccer school (6 persons), and the parents of the AMS soccer school's members (3 person). The data collecting method was used qualitative approach that was inductive analysis based on the logic principle with triangulation data. This research was conducted in three months from March to May in 2008.The result showed that AMS soccer school has not managed in a professional way yet. Generally the management in AMS soccer school especially in fostering the early age players were already apply eight management function, those are organization, planning, decision making, guiding, controlling, improvement, staff and personnel regulation and financial budqetinq. Besides, AMS soccer school was also having six management facilities, which follows: people (director and coach), financial, materials (coaching members), methods or ways, tools or facilities, and marketing. The fostering pattern and coaching which is applied by AMS soccer school in the early age players are prioritized o the playing activity and the playing which emphasized in the feeling application and motivation in order to make the children interest and like soccer. The next step was help the improvement of the children basic movement, introducing and mastering the basic technique of a playing, introducing the players role in each positions, introducing to the simple official playing roles, then they go to the physical practice, strength, endurance, agility and playing strategy.Keywords: management, the fostering of the children in the early age, AMS soccer school